A oração relativa em português sob a perspectiva discursivofuncional: interface entre a descrição e o ensino - Câmara, Aliana Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study describes the relative clauses in the Portuguese language, based on the theoretical framework of Functional Discourse Grammar (HENGEVELD; MACKENZIE, 2008). Aiming to establish the pragmatic, semantic, morphosyntactic and phonological properties of the relative clause, it was selected as the research's corpus Spoken Portuguese, representative varieties of official spoken Portuguese. It starts from the following assumptions: (i) the item that tops the relative clause contains morphological status of relative pronoun; (ii) the ordering of constituents in the relative clause follows the same principles for the placement of the constituents in the independent clause; and (iii) the relative clause can operate in organizing discursive segments. The results indicate the existence of three types of relatives: interactive, non-restrictive and restrictive. The interactive relative clause contributes to the monitoring of the interaction and consists of a Move in relation of pragmatic dependency with other Moves, being influenced by the interactional function Rescue, since recoveries the Component Contextual information. The nonrestrictive relative, in turn, is formulated as an Act in a pragmatic dependent relationship with another Act (the main clause) and it is marked by affixing rhetorical function, whose role is to give additional information about the nominal noun. A restrictive relative, unlike the others two, is defined in the Representational Level and acts as a modifier of the nominal noun and delimits a specific referent from a set of possible referents. The relative clauses are prototypically made in the categorical content frame, since it necessarily depart from information already available in the Contextual Component, the relative pronoun, which consists of a Referential Subact with the pragmatic function of topic. The difference in the formulation of the three types is reflected in...

Este estudo descreve as orações relativas nas variedades portuguesas, com base no arcabouço teórico da Gramática Discursivo-Funcional (HENGEVELD; MACKENZIE, 2008). Tendo como objetivo determinar as propriedades pragmáticas, semânticas, morfossintáticas e fonológicas da oração relativa e do item que a encabeça, seleciona-se como universo de investigação o córpus Português Falado, representativo do português como língua oficial. Parte-se das seguintes hipóteses: (i) o item que encabeça a oração relativa contém estatuto morfológico de pronome relativo; (ii) a ordenação dos constituintes na oração relativa obedece aos mesmos princípios de colocação dos constituintes na oração independente; e (iii) a oração relativa pode operar na organização de trechos discursivos. Os resultados indicam a existência de três tipos de relativas: interativa, apositiva e restritiva. A relativa interativa contribui para o monitoramento da interação e consiste em um Movimento, em relação de dependência pragmática com outros Movimentos, sendo marcada pela função interacional Resgate, já que retoma informações do Componente Contextual. A relativa apositiva, por sua vez, é formulada pragmaticamente como um Ato Discursivo em relação de dependência com outro Ato (a oração principal) e é marcada pela função retórica Aposição, cujo papel é acrescentar informação de Fundo sobre o núcleo nominal. A relativa restritiva, diferentemente das outras duas, define-se no Nível Representacional e funciona como um modificador do núcleo nominal que delimita um referente específico dentre um conjunto de referentes possíveis. As orações relativas são prototipicamente formuladas no molde de conteúdo categorial, uma vez que partem necessariamente de uma informação já disponível no Componente Contextual, o pronome relativo, que consiste em um Subato Referencial com função pragmática Tópico. A diferença no...
Keywords: Linguística; Análise linguística; Gramática discursivo funcional; Gramatica; Língua portuguesa; Linguística de corpus